The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/ic025653q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, Mechanistic, and DFT Study of the Electrophilic Reactions of Nitrosyl Complexes with Hydroxide

Abstract: We present a kinetic study of OH(-) additions to several nitrosyl complexes containing mainly ruthenium and different coligands (polypyridines, amines, pyridines, cyanides). According to a first-order rate law in each reactant, we propose a fast ion pair formation equilibrium, followed by addition of OH(-) to the [MX(5)NO](n) moieties, with formation of the [MX(5)NO(2)H](n(-1)) intermediates. Additional attack by a second OH(-) gives the final products, [MX(5)NO(2)]((n-2)). A linear plot was found for ln k(4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
144
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(170 citation statements)
references
References 70 publications
15
144
0
8
Order By: Relevance
“…[56][57][58] It should be stressed that controlling the properties of the complex, such as electronic spectra, reduction potential, and specific rate constant of the release of NO, is crucial for biological applications. [15][16][17][18][19][20][21][22][23]37,38,[59][60][61][62][63] Tetraazamacrocycles such as cyclam and its derivatives are fairly flexible; they adopt five different configurations, depending on the spatial alignment of the NH protons (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] It should be stressed that controlling the properties of the complex, such as electronic spectra, reduction potential, and specific rate constant of the release of NO, is crucial for biological applications. [15][16][17][18][19][20][21][22][23]37,38,[59][60][61][62][63] Tetraazamacrocycles such as cyclam and its derivatives are fairly flexible; they adopt five different configurations, depending on the spatial alignment of the NH protons (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[45] Depending on the metal fragments, ill-defined intermediates have been proposed in these reactions, and N 2 O and free NH 2 OH have been observed. The latter species is known to be formed by the reaction of HNO with thiols, generating the corresponding disulfide.…”
mentioning
confidence: 99%
“…29,34 It has been reported that when solutions of {MNO} 6 complexes are made alkaline, 36,40 a product with absorption band from 300 -400 nm is observed. 31,52,53 Additionally, this transformation is fully reversible upon addition of acid. Currently, there is no debate regarding the nature of this reaction corresponding to the interconversion of the nitrosyl complex into the nitrite.…”
Section: (Imn)] + With Concomitant Production Of Cis-[ru(no)(bpy) 2 (mentioning
confidence: 96%
“…Currently, there is no debate regarding the nature of this reaction corresponding to the interconversion of the nitrosyl complex into the nitrite. 31,52,53 This resulted by a nucleophilic attack of the hydroxyl into the NO + group, and a new band observed in 400 nm may be assigned to a metal to ligand charge transfer from Ru(II) to the NO 2 -ligand.…”
Section: (Imn)] + With Concomitant Production Of Cis-[ru(no)(bpy) 2 (mentioning
confidence: 99%
See 1 more Smart Citation